2022
DOI: 10.1021/acsbiomaterials.2c00111
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Mapping for Tumor Micrometastasis

Abstract: Lymph node mapping for tumor micrometastasis is of great significance for the prevention, prognosis, and treatment of cancer. Currently, the traditional clinical detection methods (computed tomography, magnetic resonance imaging, or positron emission tomography/computed tomography) in clinical lymph node mapping still have some inherent disadvantages, which have prompted the development of various fluorescent probes for lymph node mapping. However, the conventional fluorescent probes such as indocyanine green … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 112 publications
0
7
0
Order By: Relevance
“…14 Most basic research applications of FL/MR probes in lymph nodes are focused on localization, while the diagnosis of lymph node metastasis is rare. [15][16][17] Therefore, it is meaningful to develop FL/MR dual-modality probes for the diagnosis of SLN metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…14 Most basic research applications of FL/MR probes in lymph nodes are focused on localization, while the diagnosis of lymph node metastasis is rare. [15][16][17] Therefore, it is meaningful to develop FL/MR dual-modality probes for the diagnosis of SLN metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…To prevent tumor recurrence, it is crucial to correctly identify and remove lymph nodes during surgery for tumor resection. Recently, by breast cancer, which is prone to tumor metastasis, [40,95] as the model, it was found that intratumoral injection of NIR-920 NPs (Figure 11D) allowed for the fluorescence imaging of the axillary and thoracic lymph nodes. [38] Guidance by the fluorescence imaging of brachial and thoracic lymph nodes, the guided lymph nodes were precisely removed (Figure 11E).…”
Section: Image-guided Surgerymentioning
confidence: 99%
“…Lymphatic metastasis functions as a prevailing route for cancer dissemination, significantly impacting the prognosis and treatment of solid tumors, including esophageal cancer, thyroid cancer, breast cancer, and colorectal cancer. The sentinel lymph node, as the initial recipient of primary tumor drainage, furnishes essential information concerning the downstream lymph nodes. Consequently, the precise localization, visualization, and meticulous dissection of lymph nodes assume a pivotal role in cancer surgery. Direct imaging methods employed for accurate detection and identification of lymph nodes hold paramount importance in cancer diagnosis, treatment, and prognosis .…”
Section: Fluorescence Imagingmentioning
confidence: 99%